The Transformative Impact of Academic Excellence Initiatives - Salmi, Jamil (International Higher Education, 2023)
Academic Excellence Initiatives, government-sponsored programs to build world-class research-oriented universities, have become common in recent decades. These AEIs have had a significant impact on some of the countries in which they have been implemented. This article discusses the broad configurations of AEIs and addresses their success and the main problems encountered.